2015
DOI: 10.1186/s12967-015-0591-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating hematopoietic stem cells and putative intestinal stem cells in coeliac disease

Abstract: BackgroundThe intestinal stem cells (ISC) modulation and the role of circulating hematopoietic stem cells (HSC) in coeliac disease (CD) are poorly understood. Our aim was to investigate the longitudinal modifications in peripheral blood HSC traffic and putative ISC density induced by gluten-free diet (GFD) in CD.MethodsThirty-one CD patients and 7 controls were enrolled. Circulating CD133+ and CD34+ HSC were measured by flow cytometry, at enrolment and after 7 days and 1, 3, 6, 12, and 24 months of GFD. Endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Histological features including crypt hyperplasia and blunting of the villi are the hallmark of active CD characterized by expansion of the immature-cell population and concurring reduction of the mature cells of the villus 31 . These pathological manifestations of the CD intestinal mucosa have been hypothesized to be the consequence of a faulty stem cell compartment that cannot compensate the tissue turnover and/or a consequence of increased epithelium apoptosis 32,33 .…”
Section: Resultsmentioning
confidence: 99%
“…Histological features including crypt hyperplasia and blunting of the villi are the hallmark of active CD characterized by expansion of the immature-cell population and concurring reduction of the mature cells of the villus 31 . These pathological manifestations of the CD intestinal mucosa have been hypothesized to be the consequence of a faulty stem cell compartment that cannot compensate the tissue turnover and/or a consequence of increased epithelium apoptosis 32,33 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we wanted to characterize DCLK1‐positive cells in the normal human duodenal epithelium and in other parts of intestine. Additionally, to address potential stem cell‐related role of the DCLK1‐positive cells, we studied a series of patients with coeliac disease, where depletion of stem cells plays a role in pathogenesis .…”
mentioning
confidence: 99%
“…Differentiation of both absorptive and secretory epithelial cells has been shown to be affected in celiac disease. 28 , 29 When comparing our biopsy transcriptomic data to published data on single-cell RNA-Seq studies on the small intestinal epithelium, 30 we found that mature absorptive enterocyte lineage genes were almost unanimously downregulated in PGC patients. Interestingly, however, we found that genes for secretory cell signatures were upregulated during the gluten challenge ( Figure 9 A ), and most of these genes belong to the goblet cell signature.…”
Section: Resultsmentioning
confidence: 60%